Answer:
22
Step-by-step explanation:
Find f(-3) :
f(x) = x² + 2x for x ≤ -3
That means for those values of x, less than or equal to -3, this is the function.
So, f(-3) = (-3)² + 2(-3) = 9 - 6 = 3
Now, f(-1) :
From the given data, we see it is: f(x) = 2
We take this because -1 lies between -3 and 4.
Now, f(-1) = 2
=>
For f(4) :
Clearly, the function is:
Therefore, <u>f(-3) + f(-1) - f(4) = 3 + 18 - (-1) = 3 + 18 + 1 = 22.</u>
Answer:
B. 0.025
Step-by-step explanation:
Answer:
X+y=180, Y=Z, X+Z=180
Step-by-step explanation:
Hope this helps, i remember doing this lesson.
Answer:
Step-by-step explanation:
<em>First step is that you need to have the same denominators so 1/3=2/6</em>
<em>If she spent 1/6 on snacks and 2/6 on a book which means she spent 3/6</em>
<em>so the fraction of what she saved is 3/6 or 1/2</em>
Answer:
2
Step-by-step explanation:
GCF stands for the "greatest common factor." Therefore because 2 can go into both 2 and 4 evenly, it is the GCF.